Prospective CERAD Neuropsychological Assessment in Patients With Multiple System Atrophy - Maass, Fabian; Hermann, Peter; Varges, Daniela; Nuhn, Sabine; van Riesen, Christoph; Jamous, Ala; Focke, Niels K.; Hewitt, Manuel; Leha, Andreas; Bähr, Mathias; Zerr, Inga (Frontiers in Neurology, 2022)
The objective of the study was to characterize the pattern of cognitive dysfunction in patients with Multiple System Atrophy (MSA) applying a standardized neuropsychological assessment. 20 Patients with the diagnosis of probable or possible MSA were enrolled for neuropsychological assessment applying the CERAD plus battery. All patients were tested at baseline and 14/20 patients received additional follow-up assessments (median follow-up of 24 months). Additionally, relationship between cortical thickness values / subcortical gray matter volumes and CERAD subitems was evaluated at baseline in a subgroup of 13/20 patients. Trail Making Test (TMT) was the most sensitive CERAD item at baseline with abnormal performance (z-score < 1.28) in one or both pathological TMT items (TMT-A, TMT-B) in 60% of MSA patients. Additionally, there was a significant inverse correlation between the volume of the left and the right accumbens area and the TMT A item after adjusting for age (left side: p = 0.0009; right side p = 0.003). Comparing both subtypes, MSA-C patients had significant lower values in phonematic verbal fluency (p=0.04) and a trend for lower values in semantic verbal fluency (p=0.06) compared to MSA-P. Additionally, MSA-C patients showed significantly worse performance in the TMT-B task (p = 0.04) and a trend for worse performance in the TMT-A task (p = 0.06). Concerning longitudinal follow-up, a significant worsening in the TMT-B (p=0.03) can be reported in MSA. In conclusion, frontal-executive dysfunction presents the hallmark of cognitive impairment in MSA.